Diagnostic value of an immunochromatographic test over clinical predictors for tuberculosis in HIV patients - Nanta S. (2014)
Purpose: The value of an immunochromatographic test for tuberculosis (ICT-TB) combined with clinical predictors has yet to be evaluated in Thailand. This study aimed to assess any additional diagnostic value of an ICT-TB test over that of clinical predictors in a group of human immunodeficiency virus (HIV) patients as well as in subgroups of HIV patients classified by clinical risk scores. Patients and methods: An extended cross-sectional study was conducted at a community hospital in Chiang Rai and a general hospital in Lampang. HIV patients registered between April 2009 and May 2010 were screened by a locally made ICT-TB test, including 38, 16, and 6 kD Microbacterium tuberculosis antigens, as well as by routine evaluations for TB diagnosis. Demographic data, medical history, signs, and symptoms were recorded. Participants were followed up for 2 months for final ascertainment of TB diagnosis. Results: Of 206 patients, 37 (18%) had TB. Four clinical predictors were identified: low body mass index (< 19 kg/m2), prolonged cough (duration. > 2 weeks), shaking chills (≥ 1 week), and no use of antiretrovirals. The area under the receiver operating curve was 90.2%; adding the ICT-TB test result increased the area nonsignificantly to 91.6% (P =0.40). When patients were categorized by risk scores derived from selected clinical predictors into low (scores ≤ 7) and high (scores. > 7) TB risk groups, a positive ICT-TB test increased the positive predictive value nonsignificantly in the low risk group (from 12.5% to 27.3%, P =0.17) and the high risk group (from 78.6% to 80.8%, P =0.73). Conclusion: In this study setting, the ICT-TB test did not enhance TB diagnosis over the four clinical predictors in the overall group or any subgroups of HIV patients classified by clinical risk scores. © 2011 Nanta et al.